Japanese War Orphans in Manchuria - Itoh, M. author. aut Link
XXIII, 264 p.
Keywords: Japanese war orphans in Manchuria are the forgotten victims of the Asia-Pacific War and Sino-Japanese relations, and this is an integral part of the Japanese government's 'postwar settlement' issues concerning its war responsibility and compensation.